Oxalic Acid Adsorption on Rutile: Molecular Dynamics and ab Initio Calculations - Biriukov, Denys; Kroutil, Ondřej; Kabeláč, Martin; Ridley, Moira K; Machesky, Michael L; Předota, Milan (Langmuir, 2019)
Detailed analysis of the adsorption of oxalic acid ions, that is, oxalate and hydrogenoxalate, on the rutile (110) surface was carried out using molecular dynamics augmented by free energy calculations and supported by ab initio calculations. The predicted adsorption on perfect nonhydroxylated and hydroxylated surfaces with surface charge density from neutral to +0.208 C/m2 corresponding to pH values of about 6 and 3.7, respectively, agrees with experimental adsorption data and charge-distribution multisite ion complexation model predictions obtained using the most favorable surface complexes identified in our simulations. We found that outer-sphere complexes are the most favorable, owing to strong hydrogen binding of oxalic acid ions with surface hydroxyls and physisorbed water. The monodentate complex, the most stable among inner-sphere complexes, was about 15 kJ/mol higher in energy, but separated by a large energy barrier. Other inner-sphere complexes, including some previously suggested in the literature as likely adsorption structures such as bidentate and chelate complexes, were found to be unstable both by classical and by ab initio modeling. Both the surfaces and (hydrogen)oxalate ions were modeled using charges scaled to 75% of the nominal values in accord with the electronic continuum theory and our earlier parameterization of (hydrogen)oxalate ions, which showed that nominal charges exaggerate ion-water interactions.